Renaissance of Islam in North Africa: A Historical and Religious Analysis - Mustapha, Ridwan Olamilekan (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This paper explores the renaissance and development of Islam in North Africa, focusing on historical accounts and religious narratives that predate the arrival of Islam through ‘Amr bin ‘Ᾱṣ under the caliphate of ‘Umar. This study is driven by the need for a deeper understanding of how Islam in North Africa underwent historical transformations, from its early introduction to the detailed development of Islamic laws and traditions. Some historians argue that Islam was introduced earlier through migration to Abyssinia, although it was not adopted as a way of life. Other perspectives, such as Nmah (2018), highlight the role of interactions between Muslims and Christians along the Nile River as the starting point for Islamization and Arabization in the region. The paper also examines the presence of Prophet Yusuf in Egypt and the mission of Prophet Musa to the Israelites, as described in the Qur’an. These narratives indicate that Islam has been known in Egypt since ancient times, though Islamic law was not fully detailed. This study identifies four key periods in the history of Islam in North Africa: the migration to Abyssinia, the period of Prophet Yusuf, the period of Prophet Musa, and the Muslim conquest of Egypt by ‘Amr bin ‘Ᾱṣ. The study concludes that Islam's message has remained consistent since the beginning of humanity, with only the details of Shariah evolving. Future research should focus on the post-conquest period of ‘Amr bin ‘Ᾱṣ, particularly the dynamics of Islamization and Arabization and their impact on local culture and society in North Africa.